Perbandingan Densitas Energi Low-Level Laser Therapy (LLLT) 10J/cm2 dengan 5 J/cm2 terhadap Penyembuhan Luka Kaki Diabetes - Purwitasari Darmaputri; Nury Nusdwinuringtya; Nyoman Murdana; Tri Juli Edi Tarigan; Dewi Friska (Majalah Kedokteran Indonesia, 2020)
Background: Diabetic foot ulcer is a problem in patients with diabetes mellitus (DM). One adjuvant therapy that can enhance wound healing is Low-Level Laser Therapy (LLLT), but there is no established guideline regarding the dosage. In Indonesia, there has been no study comparing the energy density of LLLT on diabetic ulcer healingMethods: This is an experimental study on 28 subjects with a randomized diabetic foot ulcer. Group A received standard treatment of ulcer and LLLT 5J/cm2. Group B received standard treatment of ulcer and LLLT 10J/cm2.Results: The difference in wound size between group A and group B were 4.15 mm2 and 7.5 mm2 (p=0.178). The healing rate of group A and group B were 4.15 (-10-34.5) mm2/4 weeks and 7.5 (-2.8-34) mm2/4weeks (p=0.168).Conclusions: There was no statistically significant difference between the group receiving LLLT 5J/cm2 or 10 J/cm2 in diabetic foot ulcer healing.